Signal analysis for an entomological radar with a vertical nutating beam - Hobbs, Stephen; Allsopp, K.; Wolf, W. (Cranfield University, 2003)
This report documents the signal analysis procedures developed at Cran- field University for ground based entomological radars. The radars use a nutating vertical beam, allowing target (individual insect) position and radar crosssection (RCS) parameters to be measured The model accounts for non-circular beam cross-sections and assumes a three parameter target RCS model. An iterative maximum-likelihood algorithm is used, and uses the model and system noise data to provide quantitative measures of the model’s goodness of fit to the data and of parameter uncertainties as well as the best fit solution parameters. Successful applications of the algorithm to both radar calibration and insect monitoring are illustrated with field observations using the USDA/Cranfield ground-based entomological radar system. The results show good performance for the analysis method, but do not exploit its full potential because the noise model is only approximate.
Keywords: Radar; Insect migration; Entomological radars